2021
DOI: 10.3390/diagnostics11101894
|View full text |Cite
|
Sign up to set email alerts
|

ALADA Dose Optimization in the Computed Tomography of the Temporal Bone: The Diagnostic Potential of Different Low-Dose CT Protocols

Abstract: Objective: Repeated computed tomography (CT) is essential for diagnosis, surgical planning and follow-up in patients with middle and inner ear pathology. Dose reduction to “as low as diagnostically acceptable” (ALADA) is preferable but challenging. We aimed to compare the diagnostic quality of images of subtle temporal bone structures produced with low doses (LD) and reference protocols (RP). Methods: Two formalin-fixed human cadaver heads were scanned using a 64-slice CT scanner and cone-beam CT (CBCT). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…With acquisition settings based on our institutional stan-dards and previous literature on temporal bone EID-CT, the maximum dose reduction potential inherent in the PCD may be even greater with alternate tube potential settings. 5,30 It is important to note that lower kVp protocols with tin prefiltration (eg, Sn 100 kVp) were not included in this investigation, because they could not technically achieve the tube current-time product required for dose-equivalent comparison to 120 kVp and Sn 150/ 140 kVp protocols on either scanner. Although the energy spectrum of Sn 100 kVp is closer to that of standard 120 kVp imaging, which may be beneficial in patients with osteoporosis and for ultra-low-dose imaging tasks (eg, assessment of the paranasal sinuses), the maximum achievable radiation dose with this potential setting is far below the clinical standard for temporal bone CT. 19 Finally, it must be stated that 2 of the most advanced scanners were compared for this investigation, hence the presented image quality and radiation dose levels may not be replicable with most CT systems currently on the market.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With acquisition settings based on our institutional stan-dards and previous literature on temporal bone EID-CT, the maximum dose reduction potential inherent in the PCD may be even greater with alternate tube potential settings. 5,30 It is important to note that lower kVp protocols with tin prefiltration (eg, Sn 100 kVp) were not included in this investigation, because they could not technically achieve the tube current-time product required for dose-equivalent comparison to 120 kVp and Sn 150/ 140 kVp protocols on either scanner. Although the energy spectrum of Sn 100 kVp is closer to that of standard 120 kVp imaging, which may be beneficial in patients with osteoporosis and for ultra-low-dose imaging tasks (eg, assessment of the paranasal sinuses), the maximum achievable radiation dose with this potential setting is far below the clinical standard for temporal bone CT. 19 Finally, it must be stated that 2 of the most advanced scanners were compared for this investigation, hence the presented image quality and radiation dose levels may not be replicable with most CT systems currently on the market.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although lowering of the radiation burden remains one of the main goals in current CT research, dose reduction with the latest generation of energy-integrating multidetector and even cone-beam CT systems is hampered by constructional limitations that prevent scanners from reaching a higher geometric dose efficacy. 4,5 Ultra-high-resolution imaging in particular is limited with current detector models, because a mechanical comb filter needs to be deployed before the detector to narrow its aperture size and achieve the maximum resolution. 6 Nevertheless, dose reduction efforts in energy-integrating detector CT (EID-CT) have benefitted immensely from the introduction of spectral shaping via tin prefiltration in dual-source (and modern single-source) CT scanners.…”
mentioning
confidence: 99%
“…The TMJ acquisition protocol was as follows: field of view (FOV) of 40 × 40 mm, 90 kVp, 5 mAs and scanning time of 30.8s. The limitation of the exposure to the smallest FOV possible is in accordance to the ALARA (as low as reasonably achievable) principle, and this radiation reduction to the patient, maintaining or even improving the level of precision and accuracy in the diagnosis, supports the concept "as low as diagnostically acceptable" (ALADA) (25). Imaging features of one condyle per patient were included to reduce possible bias due to non-specific side data in systemic biological samples and comorbidities, technical problems in the hr-CBCT image acquisition, and presence of unilateral TMJ OA.…”
Section: Imagingmentioning
confidence: 59%
“…High-resolution computed tomography (HRCT) is the gold standard for imaging the temporal bone. This method provides crisp, clear images of the bony structure with radiation doses ranging from 1.6 mSv for adults to 7.1 mSv for new-borns, an amount equivalent to 6–24 months of background radiation [ 8 , 12 ]. CBCT can produce images that are as good or even better [ 5 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…As early as 15 years ago, Peltonen et al [5] demonstrated the substantial potential of CBCT for imaging the middle ear; however, multi-slice computed tomography (MSCT) is still the standard method. The most recent articles rank CBCT as equal or superior to MSCT in terms of image quality (IQ) and resolution [6][7][8]. However, these studies compared images of cadaver heads and are thus free of reallife motion artifacts.…”
Section: Introductionmentioning
confidence: 99%